Business restriction in fiscal policy: The Mexican case of 1972-1976 - Castañeda, Gonzalo (Estudios Económicos de El Colegio de México, 1993)
This paper presents a model grounded on game theory with incomplete information to explain some economic events that took place in Mexico during the Echeverría administration. These are the aborted fiscal reform of 1972 and the deterioration in the relationship between the government and the private sector from 1973 to 1976 (represented by excessive government expenditures, capital flight, inflation and low investment).